Classroom research and professional development (2009)
This article intends to share the experience of a group of teachers in the Classroom Research Seminar of the Teacher Development Program in English carried out at Universidad del Valle, Cali, from January to June, 2007. The seminar was part of a high-level in-service program for teachers of English of a network of private educational institutions. We would like to share the highlights and difficulties of the experience. We will start with the general framework of the program and the concept of professional development that underlies it. Next we will focus on the classroom research seminar, its objectives, methodology and results. Finally we share the voices of some of the participants, who talk about the influence this seminar had on their professional development and daily work. Key words: Classroom research, teacher development, teacher researcher, educational research Este artículo recoge la experiencia de un grupo de profesores universitarios que tuvieron a su cargo el seminario de investigación en el aula con un grupo de docentes inscritos en el programa de formación y desarrollo profesional docente de la Universidad del Valle y pertenecientes a una misma red de instituciones. Nuestro objetivo es compartir los logros y dificultades encontradas en el proceso de trabajar con los docentes, desde el aula universitaria, problemáticas de sus propias aulas a partir de objetivos e intereses diversos. Primeramente presentaremos el marco general del programa y el concepto de formación que lo sustenta; posteriormente nos centraremos en el contexto específico del seminario, sus objetivos metodología y procesos de desarrollo; finalmente exploraremos la incidencia del trabajo desarrollado en el aula universitaria en práctica profesional de los docentes participantes. Palabras clave: Investigación en el aula, desarrollo profesional docente, docente-investigador, investigación educativa